SAYYID QUTB: PRINCIPLES AND IDEALISM OF THE MOVEMENT - Ahmad Nabil Amir; Tasnim Abdul Rahman (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2025)
The paper aims to analyzes the principal ideas and influence of Sayyid Qutb as the leading member and ideologue of Ikhwan al-Muslimun (the Muslim Brotherhood), a major Islamic movement in Egypt. As political theorist and revolutionary, his influence and presence in the movement was highlighted by his inspiring role and struggle in the formulation of its doctrine and ideological roots. His ideas had widely influenced the activist of the Muslim Brotherhood at every level and contributed at mobilizing a strong cadre that represent its strength and driving force. The study is based on historical approaches, using heuristic, source criticism, interpretation and historiographical methods. The finding shows that Sayyid Qutb had left an indelible mark in the movement through his productive works and writings that were instrumental in the formation of ideas and in defining the Society’s vision that have become references and mandatory texts in the movement. His intellectuality has become a source of inspiration in the movement in the making of its political activism and the shaping of its ideas toward viewing Islam in its totality and redefining the Society’s role in term of its ideals and priorities.